Tunisia Urban Development and Local Governance Program : Technical Assessment Report - World Bank (Washington, DC, 2014)
In this context, the reform of the LG capital grants and municipal investment planning framework forms the main strategic actions undertaken by the government towards the implementation of its decentralization agenda recently anchored in the new Constitution adopted in January 2014. This grant system, which had operated under an ex ante system of controls, is being restructured through the revision of the Decree 97-1135 governing the LG capital grant system. Through the restructuring, the government intends to improve the efficiency of the state financial support to municipal investment, make the allocation of capital grants more transparent and predictable, strengthen the decision-making power of LGs on the use of their investment funding, and progressively introduce a performance based dimension to their capital grant system. Along with revision of the above decree, the government has also issued a Ministerial Decree to introduce participatory municipal investment planning and budgeting systems, hence promoting citizen engagement in identifying investment needs and priorities. Under the same reform, the government will progressively introduce an independent, annual assessment to measure the performance of LGs in line with the above amended decree. The performance assessment system, in addition to serving as a tool for monitoring LG s performance, has proven to be a very effective means of incentivizing LGs to strengthen their institutional performance, where access to grant funds is linked to results. The areas covered under the performance assessment will include governance, sustainability and management. The results of this performance assessment will be used to adjust the capital grant allocation starting the third year of the program.